2019
DOI: 10.1007/s00261-019-01919-2
|View full text |Cite
|
Sign up to set email alerts
|

False positives in PIRADS (V2) 3, 4, and 5 lesions: relationship with reader experience and zonal location

Abstract: Purpose To investigate the effect of reader experience and zonal location on the occurrence of false positives (FPs) in PIRADS (V2) 3, 4, and 5 lesions on multiparametric (MP)-MRI of the prostate. Materials and methods This retrospective study included 139 patients who had consecutively undergone an MP-MRI of the prostate in combination with a transrectal ultrasound MRI fusion-guided biopsy between 2014 and 2017. MRI exams were prospectively read by a group of inexperienced radiologists (cohort 1; 54 patients)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 33 publications
0
24
0
Order By: Relevance
“…Furthermore, mpMRI can be incorporated into the practical pathway and guide the decision regarding active surveillance [ 4 ]. However, the limited PPV and CDR of PI-RADSv2.0 for csPCa was associated with overestimation, resulting in the risk of unwarranted targeted biopsies [ 5 7 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, mpMRI can be incorporated into the practical pathway and guide the decision regarding active surveillance [ 4 ]. However, the limited PPV and CDR of PI-RADSv2.0 for csPCa was associated with overestimation, resulting in the risk of unwarranted targeted biopsies [ 5 7 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…The authors indicated that the dominant cancer location in the peripheral zone might explain the differential cancer detection rates by zone. Additionally, in this study, the lower PI‐RADS score in the TZ and central zone could have contributed to the lower cancer detection rate in these zones . Intriguingly, the false positive rate was higher in the TZ, especially among inexperienced radiologists, indicating that foci in the TZ can easily be overdiagnosed as suspected cancer .…”
mentioning
confidence: 66%
“…Additionally, in this study, the lower PI‐RADS score in the TZ and central zone could have contributed to the lower cancer detection rate in these zones . Intriguingly, the false positive rate was higher in the TZ, especially among inexperienced radiologists, indicating that foci in the TZ can easily be overdiagnosed as suspected cancer . The false positive rate in the TZ by MRI might therefore be improved as radiologists’ experience increases.…”
mentioning
confidence: 70%
See 1 more Smart Citation
“…They also showed that zonal location was not significantly associated with false-positive results. 20 Truong et al used datasets from two different centres (the University of Rochester Medical Center [URMC] and the University of Alabama at Birmingham [UAB]) in their multicentre study. 12 The final nomogram (URMC + UAB) was created by combining the datasets of both centres, and we used that for comparative analysis.…”
Section: Model Discrimination and Calibrationmentioning
confidence: 99%